High resolution electron microscopy of enamel crystals in cases of human dental fluorosis - Yanagisawa, T; Takuma, S; Tohda, H; Fejerskov, O; Fearnhead, R W (Journal of electron microscopy, 1989)
Surface enamel from human subjects with dental fluorosis was studied by means of high-resolution transmission electron microscopy. Immediately below the relatively highly mineralized outermost surface enamel layer was an extensive hypomineralized area. The highly mineralized layer was composed of many large elongated hexagonal crystals and extremely small hexagonal crystals. Frequently the small crystals were attached to the periphery of the large crystals. In the hypomineralized area, large crystals were sparsely arranged; and a few small crystals were seen. Some large crystals showed either perforated centers or defects on their peripheries. These findings suggest that the hypomineralized area undergoes caries-like changes in terms of crystal dissolution and that the highly mineralized surface layer is either formed or modified by remineralization.